أحكام النفقة الزوجية في الفقه الإسلامي - الأطرش, أحلام (University of Eloued جامعة الوادي, 2017)
تناولت هذه الدراسة أحد أهم الجوانب التي تكون مثار خلاف و شقاق بين أفراد الأسرة الواحدة، ويتعلق ذلك بنفقة الزوجة، التي هي أثر من آثار عقد الزواج ، وحق مالي للزوجة بعد تمام العقد الصحيح ، و التزام مستمر يقع على عاتق الزوج. حيث يهدف هذا الموضوع إلى التعرف على بعض الأحكام الخاصة بالنفقة الزوجية ولو بصورة عامة ، فتناولت في المبحث الأول: مفهوم النفقة الزوجية و حكمها الشرعي أما المبحث الثاني: فكان عنوانه شروط و أسباب استحقاق الزوجة للنفقة وأنواعها. أما المبحث الثالث والأخير فقد تناولتُ فيه أحوال استحقاق الزوجة للنفقة و حالات سقوطها وخلص البحث إلى جملة من النتائج أهمها: -أن المقصود بالنفقة كل ما تحتاج إليه الزوجة لمعيشتها من طعام وكسوة ومسكن وغيرها. -أن سبب وجوب النفقة هو كونها زوجة له بالتمكين لا بمجرد العقد. -وجوب نفقة الزوجة على الزوج بنص القرآن الكريم و نص الحديث النبوي الشريف طيلة بقاء الحياة الزوجية و بعدها أيضا خلال فترة العدة من الطلاق و التفريق. -كذلك أن من القواعد المقررة فقهاً أن من حبس لحق غيره فنفقته واجبة على ذلك الغير وأن المرأة إذا حبست على الزوج للقيام على البيت ورعاية شؤونه، وفرغت نفسها لمنفعة زوجها فتكون نفقها واجبة عليه. -بالإضافة إلى أن ما يعتبر في تقدير النفقة هو اعتبار حال الزوج من اليسر والعسر. This study dealt with one of most important aspects that are controversial and split among members of the same family , and this is related to the alimony of the wife , which is the effect of the marriage contract, and the husband’s potenti al after the completion of the right contact , and the continuous commitment falls on the husband . Where the purpose of this subject identify some provisions for marital alimony and even in general. I dealt with the first topic :the concept of alimony and its legal ruling. The second topic :the conditions and the reasons of the wife’s benefit for alimony and its types . The last topic : conditions of eligibility of the wife’s benefit for alimony and the in cidente of its falling. The research reached a number of results , the most important are : The husbands obligation of expence for the wife in the text of Holy Quran and the text of Hadith Throughout the life of marriage and after it , during the period of the divorce and the separation. Furthermore, one of the prescribed rules is that the person who is imprisoned for the right of another is exempted from doing so. If the woman is confined to the husband to perform the house and take care of his affairs, and she has provided herself for the benefit of her husband In addition, what is considered in the estimate the alimony is to consider the husband's condition of ease and hardship.
مذكرة ماستر تخصص اصول فقه
Keywords: الأحكام، نفقة الزوجة، شروطها، أسبابها، أنواعها.; provisions ، of expenece for the wife ، condition، reasons، fall